Plato's epistemology being and seeming - Moss, Jessica 1973- (Oxford University Press, 2021)
Plato's Epistemology presents an original interpretation of one of the central topics in Plato's work: epistemology. Moss argues, against the grain of much modern scholarship, that Plato's epistemology is radically different from our own
Keywords: Plato -- v427-v347; Erkenntnistheorie; Electronic books